2016
DOI: 10.1039/c5fo01560j
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D increases the gene expression of enzymes protecting from glucolipotoxicity in peripheral blood mononuclear cells and human primary endothelial cells

Abstract: Besides its classical function as an orchestrator of calcium and phosphorus homeostasis, vitamin D also affects insulin secretion and tissue efficiency. A number of studies have consistently reported the inverse relationship between vitamin D deficiency and type 2 diabetes. Activation of certain metabolic pathways and down-stream transcription factors may protect from glucolipotoxicity and their targeted activation -e.g. by vitamin D - might explain the detrimental role of vitamin D deficiency in diabetes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…With respect to previous studies, over expression of GLO1 can effectively reduce AGEs formation [35]. In this study, the GLO1 expression level in PBMCs of T2DM indicated no change after receiving vitamin D. Up to now; only one study has examined the vitamin D effect on GLO1 expression with conflicting results in different cells [13]. Therefore, further studies are required in this field.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…With respect to previous studies, over expression of GLO1 can effectively reduce AGEs formation [35]. In this study, the GLO1 expression level in PBMCs of T2DM indicated no change after receiving vitamin D. Up to now; only one study has examined the vitamin D effect on GLO1 expression with conflicting results in different cells [13]. Therefore, further studies are required in this field.…”
Section: Discussionmentioning
confidence: 65%
“…Human glyoxalase I is a dimeric Zn (2+) metalloenzyme, and was expressed in different cell types like immune cells and endothelial cells. Glyoxalase-1 increased expression reduces the inflammatory and oxidative processes that were caused by AGEs [13, 14]. It has also been indicated that TNF-α is a RAGE gene expression regulator [15].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D was also reported to exert a protective role against glycative stress [210,211]. Vitamin D supplementation in type-2 diabetes participants showed a trend in increasing GLO1 expression, a transcriptional downregulation of RAGE receptor and decreased in AGE serum in a double-blind randomized placebo-controlled [211].…”
Section: Vitaminsmentioning
confidence: 97%
“…61 It may also play a protective role against glucolipotoxicity, with one in vitro study supporting 1,25(OH)D in the regulation of key enzymes involved in protective pathways. 62 Given these findings, and the documented low 25(OH)D levels during pregnancy, it is plausible that the increased prevalence of GDM in asthma is mediated via lower 25(OH)D levels, reducing insulin secretion and, consequently, increasing blood glucose levels.…”
Section: Vitamin D and Pregnancymentioning
confidence: 99%
“…61 It may also play a protective role against glucolipotoxicity, with one in vitro study supporting 1,25(OH)D in the regulation of key enzymes involved in protective pathways. 62…”
Section: Potential Links Between Asthma and Gestational Diabetes Mellitusmentioning
confidence: 99%